Issues of diagnosis and treatment of metastases in the spine and long bones - A. V. Bukharov; D. A. Erin; V. A. Derzhavin; A. V. Yadrina (Сибирский онкологический журнал)
Purpose: to conducted a systematic analysis of data available in the current literature, modern diagnosticalgorithms, prognostic factors, survival and options for surgical treatment of metastases in the spine andlong bones of the extremities.Material And Methods. The review included data from randomized clinical trials evaluating various diagnostic algorithms for detecting bone metastases, the frequency of metastases to the vertebral column and long bones, their number, and options for surgical or radiation treatment published over the past 10 years. The review also evaluated various prognostic factors that can be used to determine the patient’s life expectancy.Results. Diagnostic algorithms and scales that help choose treatment strategy, taking into account prognostic factors, were published. The treatment outcomes in patients with spine and long bone metastases were shown to be improved due to personalized surgical treatment strategies.Conclusion. Further studies are needed to identify new prognostic factors determining the oncological outcomes in patients with bone metastases. This will lead to the optimization of surgical treatment methods and the development of new algorithms for choosing the extent of surgery in patients with bone metastases.